N-Heterocyclic carbene-stabilized gold nanoparticles with tunable sizes. Issue 19 (4th May 2018) - Bridonneau, N.; Hippolyte, L.; Mercier, D.; Portehault, D.; Desage-El Murr, M.; Marcus, P.; Fensterbank, L.; Chanéac, C.; Ribot, F.
Abstract : A simple and direct way to NHC-protected gold nanoparticles with tuned sizes. Abstract : A simple and straightforward synthesis of N-heterocyclic carbene (NHC)-protected gold nanoparticles is derived from (benz)imidazolium-AuX4 complexes and NaBH4 only. The proposed method allows size tuning, from 3 to 6 nm, by adding (benz)imidazolium bromide. Changing the reducing agent to t BuNH2 BH3 shifts the size range to ca. 6–12 nm. A one pot protocol is also reported from AuCl, (benz)imidazolium bromides and NaBH4, thereby providing an even more straightforward way of producing NHC-capped gold nanoparticles. In addition, X-ray photoelectron spectroscopy (XPS) is used to unambiguously evidence, on the nanoparticles, the covalent bond formed between the NHC and the surface gold atoms.